Nilai dan Makna Tarian Tebe di Desa Babotin Maemina Kecamatan Botin Leobele Kabupaten Malaka - Intan Mutiara Iriani Romiro; Yohanis K. Tampani; Antonius Bere; Yuditha Sofiana Kofi; Augusta De Jesus Magalhaes (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2024)
This research was conducted by Intan Mutiara Iriani Romiro with the title "The Values and Meaning of Tebe Dance in Babotin Maemina Village, Botin Leobele District, Malaka Regency." The aim of this study is to reveal the values and meaning of the Tebe Dance performed by the community in Babotin Maemina Village. Tebe Dance is a cultural heritage rich in traditional values passed down from generation to generation. This dance not only serves as an artistic expression but also as a means of social communication that strengthens the sense of togetherness and the identity of the local community. The research method used is descriptive qualitative with an ethnographic approach. Data collection was carried out through in-depth interviews with cultural figures, dancers, and direct observation of the dance performance. In addition, literature studies were utilized to enrich the understanding of the cultural and historical context of the dance. The results of the study indicate that Tebe Dance embodies important values such as togetherness, respect for ancestors, as well as symbols of unity and cultural identity. The philosophical meaning of the movements in the Tebe Dance also reflects a harmonious relationship between humans and nature, as well as among community members. In conclusion, Tebe Dance functions not only as entertainment or ritual but also as a medium to strengthen social solidarity and preserve the cultural identity of the Babotin Maemina community. Therefore, efforts to preserve and reintroduce these values to younger generations are essential to ensure they remain intact in the future.